RESEÑA de : Tessicini, D.; Boner, P.J. (Eds.). Celestial Novelties on the Eve of the Scientific Revolution 1540-1630. Florencia: Leo Olschki, 2013 - Solís, Carlos (ENDOXA, 2013)
(Publicado por el Museo Galileo de Florencia con ayuda del Ministerio de Economía de España).